Peter block flawless consulting : - Block, Peter (Jossey-Bass/Pfeiffer, 2000)
Peter Block covers the intangibles of consulting: the politics, communications and the obstacles that derail the consultant/client relationship. This book is a MUST read, not only for consultants, but for anyone that works in or around companies that have politics, or bureaucracy, or people. That should cover just about all of us. This book helped me because it covered so much more then the business techniques of consulting, hey I'm a business consultant after all. Flawless Consulting helps you master communication and contracting gaffs, to understand why after much good advice the customer still does the wrong thing, and most importantly how your success can be assured despite those kind of issues.